Penerapan Manajemen Karakter dan Kepemimpinan pada Siswa Pondok Pesantren Wasilatul Abror - Tifani Dame Hasany; Dhanny Safitri; Dinis Cahyaningrum; Isra Dewi Kuntary Ibrahim; Ni Wayan Adelia Mutiara Asri; Dina Amalya Putri; Siti Anggriana; M. Jumaedi (North Press, 2025)
This community service activity aimed to strengthen character management and leadership among students (santri) at Pondok Pesantren Wasilatul Abror. Islamic boarding schools play a strategic role in shaping generations who are not only intellectually competent but also disciplined, ethical, and capable of leadership. However, the challenges of globalization demand more structured character and leadership development so that students can adapt to social changes while upholding Islamic values. The program was held on at the Wasilatul Abror Islamic Boarding School Hall, involving students from elementary to secondary levels. The methods applied included interactive lectures, sharing sessions, mentoring, and leadership games based on experiential learning. The results showed high enthusiasm among students, active participation in discussions, and improvement in discipline, responsibility, and teamwork skills. The activity effectively enhanced students’ awareness of self-management and integrity-based leadership. It is recommended that similar programs be conducted regularly to ensure the sustainability of character and leadership development within the pesantren environment.